Golden Trail: Retrieving the Data History that Matters from a Comprehensive Provenance Repository - Paolo Missier; Bertram LudÃ¤scher; Saumen Dey; Michael Wang; Tim McPhillips; Shawn Bowers; Michael Agun; Ilkay Altintas (International Journal of Digital Curation, 2012)
Experimental science can be thought of as the exploration of a large research space, in search of a few valuable results. While it is this â€œGolden Dataâ€ that gets published, the history of the exploration is often as valuable to the scientists as some of its outcomes. We envision an e-research infrastructure that is capable of systematically and automatically recording such history â€“ an assumption that holds today for a number of workflow management systems routinely used in e-science. In keeping with our gold rush metaphor, the provenance of a valuable result is a â€œGolden Trailâ€. Logically, this represents a detailed account of how the Golden Data was arrived at, and technically it is a sub-graph in the much larger graph of provenance traces that collectively tell the story of the entire research (or of some of it).